2022
DOI: 10.1093/trstmh/trac027
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trend, space risk and factors associated with the occurrence of dengue in northeast Brazil, 2009–2018

Abstract: Background Dengue is an acute viral disease of major relevance and impact on public health, causing major epidemics around the world, especially in tropical regions. Here we aimed to analyse the temporal trend and spatial risk, as well as social vulnerability factors, associated with the occurrence of dengue in the state of Bahia, Brazil between 2009 and 2018. Methods This is an ecological study carried out with all suspected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…As in the case of deforestation, studies carried out in Brazil have not shown a consistent pattern regarding which socioeconomic factors most strongly influence the number of dengue cases. However, this disease is usually positively affected by a high inequality in income distribution and low education [67,[72][73][74]. Despite this, Morais [66] found a greater number of cases in municipalities with a higher GDP in the Atlantic Forest of Minas Gerais, suggesting that, often, even richer municipalities do not prioritize basic sanitation and health care.…”
Section: Discussionmentioning
confidence: 99%
“…As in the case of deforestation, studies carried out in Brazil have not shown a consistent pattern regarding which socioeconomic factors most strongly influence the number of dengue cases. However, this disease is usually positively affected by a high inequality in income distribution and low education [67,[72][73][74]. Despite this, Morais [66] found a greater number of cases in municipalities with a higher GDP in the Atlantic Forest of Minas Gerais, suggesting that, often, even richer municipalities do not prioritize basic sanitation and health care.…”
Section: Discussionmentioning
confidence: 99%
“…As in the case of deforestation, studies carried out in Brazil have not shown a consistent pattern regarding which socioeconomic factors most strongly influence the number of dengue cases. However, this disease is usually positively affected by high inequality in income distribution and low education (ALVES 2015, CARMO et al 2020, SOUSA et al 2021, COUTINHO et al 2022. Despite this, Morais (2011) found a greater number of cases in municipalities with higher GDP in the Atlantic Forest of Minas Gerais, suggesting that, often, even richer municipalities do not prioritize basic sanitation and health care.…”
Section: Discussionmentioning
confidence: 99%
“…The transmitting agent is the female Aedes aegypti mosquito, and its transmission occurs through its bite, passing the virus to the host. The individual may develop the disease or not 4 . Dengue affects thousands of people each year in several countries, including Brazil and other regions of Latin America 5 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The epidemiological situation of dengue in Brazil and Latin America is complex and challenging, as the disease is endemic in many areas and transmission can be influenced by factors such as climate change, urbanization and population migration 2 . Dengue control requires a multifaceted approach that involves prevention measures, early detection and adequate treatment of cases, thus understanding how climate variations affect this transmission is of paramount importance for understanding the vectors 4 , 10 .…”
Section: Introductionmentioning
confidence: 99%